2015
DOI: 10.1186/s12985-015-0409-y
|View full text |Cite
|
Sign up to set email alerts
|

A model with combined viral and metabolic factors effectively predicts HBeAg status under long term entecavir therapy: a prospective cohort study

Abstract: Background & AimThe aim was to extract factors from virologic and biochemical profiles at baseline and 24 weeks of treatment to predict HBeAg seroconversion in patients treated with ETV.MethodsHBeAg positive chronic hepatitis B patients receiving ETV naïve-treatment were enrolled. HBV DNA, ALT, and serological markers were prospectively monitored every 6 months for 240 weeks. The cumulative rates of virologic response (VR), biochemical response (BR), and HBeAg seroconversion were determined, and potential pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“… 13 Another study showed that the HBeAg/anti-HBe seroconversion rate was 36.7% with 5-year ETV treatment in HBeAg-positive CHB. 17 In an ETV 7-year treatment study, HBeAg/anti-HBe seroconversion rates at years 3 and 7 were 26.7% and 37.5%, respectively. 18 Additionally, many investigations have shown that ETV and LDT have a higher rate of HBeAg/anti-HBe seroconversion in patients with HBeAg-positive CHB.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 13 Another study showed that the HBeAg/anti-HBe seroconversion rate was 36.7% with 5-year ETV treatment in HBeAg-positive CHB. 17 In an ETV 7-year treatment study, HBeAg/anti-HBe seroconversion rates at years 3 and 7 were 26.7% and 37.5%, respectively. 18 Additionally, many investigations have shown that ETV and LDT have a higher rate of HBeAg/anti-HBe seroconversion in patients with HBeAg-positive CHB.…”
Section: Discussionmentioning
confidence: 93%
“…It also agrees with previous reports of baseline ALT >5 ULN as a positive predictor for HBeAg seroconversion, 13 , 14 and serum HBV DNA <9 log 10 copies/mL as a strong predictor for better virological outcomes. 13 17 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the association between pretreatment alanine aminotransferase (ALT), HBV DNA, hepatitis B surface antigen (HBsAg), quantitative HBeAg (qHBeAg), platelets (PLT), gamma-glutamyl transpeptidase (GGT), and quantitative anti-hepatitis B core antibody (qAnti-HBc) levels with HBeAg seroconversion (Chi et al, 2015;Fan et al, 2016;Fried et al, 2008;Li et al, 2014;Wang et al, 2015a;Hou et al, 2015;Huang et al, 2015). Although several clinically useful models have been established for assessing HBeAg seroconversion, they require complex calculations or concentrate on the response to interferon (Wang et al, 2015b;Lee et al, 2014;Lee et al, 2011;Liu et al, 2015). Thus, it appears that no other study has developed a multiparameter scoring model to clearly define the relationships between these factors.…”
Section: Introductionmentioning
confidence: 99%